Lepiota atrobrunneodisca (Agaricaceae, Agaricales), a new species with a hymeniform pileus covering from North China - Mao, Ning; Xia, Lu; Xu, Yu-Yan (Phytotaxa, 2023)
Lepiota atrobrunneodisca sp. nov. is described and illustrated based on collections from Shanxi Province in North China. This species is characterized by the pileus with dark brown to black-brown umbonate disc, irregularly shaped squamules on a whitish surface, annulus often adhering to stipe, ellipsoid to narrowly ellipsoid, binucleate basidiospores, numerous cheilocystidia, the absence of pleurocystidia, and the hymeniform pileus covering made up of tightly packed subglobose, sphaeropedunculate to clavate terminal elements. The phylogenetic analyses were performed using ITS and four combined loci (ITS-nrLSU-IGS-mtSSU) datasets, which supported that L. atrobrunneodisca formed a distinct clade.